MAKNA KOMUNIKASI PADA SIMBOL BUDAYA DALAM TARIAN LULO DI KONAWE SELATAN - Asrul Jaya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
Almost all human statements either intended for his own interests or for the benefit of others are expressed in symbolic form. The relationship between the parties involved in the communication process is largely determined by the symbols or symbols used in communicating. Symbols can be expressed in the form of spoken or written language (verbal) or through certain cues (non verbal). Symbols carry a statement and are given meaning by the recipient; because it gives meaning to the symbol used in communicating is not an easy thing, but a problem that is quite complicated. The process of giving meaning to the symbols used in communicating, in addition, influenced by cultural factors, as well as psychological factors, especially when the message is decoded by the recipient. A message delivered with the same symbol may differ in meaning when the individual receiving the message differs within the frame of mind and experience frame. Lulo as a traditional dance has a big meaning and portrays the unity of Tolaki community in diversity by leaving a barrier that distinguishes social status as well as being a means of finding a mate. The tradition of lulo shows the nature of friendship and mutual cooperation that is characteristic of the Tolaki community. Keywords: meaning, communication, cultural symbol, lulo dance